Biomimetic design and development of a hexapedal running robot with automatic gaiting selection based on terrain - Ma, Tien Choon; H. M. Amin, Shamsudin (2005)
Animals inspire our intuition that legs may be necessary for satisfactory exploration of highly broken and unstable landscapes. Gaiting style is the next crucial element in determining mobility of the legged robot as special gaits improve the mobility of the robot drastically and permit the robot to climb over small obstacles or cross broken terrain more efficiently. The aim for this research is to design and develop an automatic gaiting selection system which decides the gaits of the robot according to the environments using embedded vision system. The proposed method has been tested on the Hexapedal Running Robot and result is discussed in this paper.